Beyond Intra-modality: A Survey of Heterogeneous Person Re-identification - Wang, Zheng; Wang, Zhixiang; Zheng, Yinqiang; Wu, Yang; Zeng, Wenjun; Satoh, Shin’ichi (International Joint Conference on Artificial Intelligence (IJCAI) (Survey Track), 2020)
.